Fantômes - Civeyrac, Jean-Paul, 1964-; Ferreira, Dina; Lelouch, Emilie, 1976-; Verdier, Guillaume (Les Films Pelléas, 2001)
At the beginning of the third millennium occurs at Paris an unexpected phenomenon. People inexplicably disappear and remain missing. --